Welcome to Westonci.ca, the place where your questions find answers from a community of knowledgeable experts. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.

Which shows the correct substitution of the values a, b, and c from the equation 0 = 4x2 + 2x – 1 into the quadraticformula below?Quadratic formula: x = -bt/b2 - 4 ac2aOX=-222 - 4(4)( - 1)2(4)0x =-2 V22 - 4(4)(1)2(4)OX=-2 V22 + 4(4)(-1)2(4)x =-2-22-4(4)(-1)2(4)

Sagot :

The equation

[tex]4x^2\text{ + 2x -1 = 0}[/tex]

comparing it with the standard quadratic equation

[tex]ax^2\text{ + bx + c = 0}[/tex]

a=4 b=2 and c=-1

The quadratic formula is given by

[tex]X=\text{ -b }\pm\frac{\sqrt{b^2\text{ +4ac}}}{2a}\text{ }[/tex]

substituting a=4 b=2 and c= -1 into the quadratic formula

[tex]\text{ X = -2 }\pm\frac{\sqrt{2^2+4(4)(-1)}}{2(4)}[/tex]